Control gubernamental del gasto público en el Estado constitucional: reflexiones a propósito de la aprobación de las facultades sancionadoras de la Contraloría General en materia de responsabilidad administrativa funcional - García Cobián Castro, Erika (2013)
Constitutional doctrine has little addressed on the General Comptroller of the Republic and its controlling function of public resources execution and management. Efforts have been made to explain this situation in other realities, regarding high budgetary, accounting and auditing content needed to carry out auditing activities constitutionally assigned to this kind of entities. Nevertheless, identifying competences of the General Comptroller of the Republic and its nature of autonomous constitutional body shapes an important expression of Constitutional State and the principle of powers division. This entity controls State’s Public Budget execution contributing to constitutional property protection, legality of budget implementation and the appropriate management of public resources, also the «efficiency» of social needs, proper functioning of public administration and prevention of corruption, among others duties. This article analyzes the constitutional mission of the General Comptroller in a Constitutional State promoting the process of given a constitutional status to the legal system in its area of influence, also optimizing constitutional properties protected. For such purpose, the 29622 recent law («Law that modifies the 27785 Organic Law of National Control System and the General Comptroller of the Republic extending powers in order to sanction in accordance of functional administrative responsibility») shall be used as object of constitutional analysis.